Synaptic activity is not required for establishing heterogeneity of inner hair cell ribbon synapses - Karagulyan, Nare; Moser, Tobias (Frontiers in Molecular Neuroscience, 2023)
Neural sound encoding in the mammalian cochlea faces the challenge of representing audible sound pressures that vary over six orders of magnitude. The cochlea meets this demand by active micromechanics as well as by diversity and adaptation of afferent neurons and their synapses. Mechanisms underlying neural diversity likely include heterogeneous presynaptic input from inner hair cells (IHCs) to spiral ganglion neurons (SGNs), differences in molecular profile of SGNs and in their efferent control. Here, we tested whether glutamate release from IHCs, previously found to be critical for maintaining different molecular SGN profiles, is required for establishing heterogeneity of active zones (AZs) in IHCs. We analyzed structural and functional heterogeneity of IHC AZs in mouse mutants with disrupted glutamate release from IHCs due to lack of vesicular glutamate transporter (Vglut3) or impaired exocytosis due to defective otoferlin. We found the variance of the voltagedependent activation of presynaptic Ca 2+ influx to be reduced in exocytosis-deficient IHCs of otoferlin mutants. Yet, the opposing spatial gradients of maximal amplitude and voltage-dependent activation of Ca 2+ influx along the modiolar-pillar IHC axis were maintained in both mutants. Further immunohistochemical analysis showed an intact modiolar-pillar gradient of ribbon size in Vglut3 -/- mice. These results indicate that IHC exocytosis and glutamate release are not strictly required for establishing the heterogeneity of IHC AZs.